2008
DOI: 10.2147/ppa.s4163
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of primary open-angle glaucoma: Best practices associated with enhanced patient compliance and persistency

Abstract: Primary open angle glaucoma is a chronic optic neuropathy often requiring lifelong treatment. Patient compliance, adherence and persistence with therapy play a vital role in improved outcomes by reducing morbidity and the economic consequences that are associated with disease progression. A literature review including searches of The Cochrane Library, MEDLINE, PubMed, conference proceedings, and bibliographies of identified articles reveals the enormous public health burden in various populations due to the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
3
30
0
2
Order By: Relevance
“…To be clinically relevant, an 'acceptable' adherence level should be determined by its impact on clinical outcome. 10 Such evidence is lacking for ocular hypotensives due to the requirement for long-term follow-up and known inaccuracies in determining IOP control, 12 visual field defects, or optic nerve damage. However, a recent cross-sectional glaucoma study in the United States found that participants with adherence rates o80%, according to a medication event monitoring system (MEMS), had worse visual field defects than those with adherence rates Z80%.…”
Section: Introductionmentioning
confidence: 99%
“…To be clinically relevant, an 'acceptable' adherence level should be determined by its impact on clinical outcome. 10 Such evidence is lacking for ocular hypotensives due to the requirement for long-term follow-up and known inaccuracies in determining IOP control, 12 visual field defects, or optic nerve damage. However, a recent cross-sectional glaucoma study in the United States found that participants with adherence rates o80%, according to a medication event monitoring system (MEMS), had worse visual field defects than those with adherence rates Z80%.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the preservatives present in these medications cause the development of, or exacerbates, OSD. Preservative-induced OSD causes ocular discomfort and dryness and may account for non-compliance to glaucoma treatment 53 (up to 64% in one study). 54 The development of preservative-free topical anti-glaucoma medications such as Timabak (Théa, Paris, France) and Zioptan (Merck, Whitehouse Station, NJ, USA) has provided a solution to avoid the adverse effects of preservatives.…”
Section: Discussionmentioning
confidence: 99%
“…How this may occur is unknown. As to clinical relevance, studies reveal that patients are highly complaint to tailored exercise regimens (mean age of 70 [39][40][41][42][43] ) and that RD patients are nearly 100% compliant in following tailored prescriptions from retina specialists. 41 This suggests that RD patients may benefit more from exercise than other patient groups as they may adhere to exercise "prescriptions.…”
Section: Exercise May Be Beneficial To Retina and Visionmentioning
confidence: 99%